Topological Data Analysis as a Morphometric Method: Using Persistent Homology to Demarcate a Leaf Morphospace - Li, Mao; An, Hong; Angelovici, Ruthie; Bagaza, Clement; Batushansky, Albert; Clark, Lynn; Coneva, Viktoriya; Donoghue, Michael J.; Edwards, Erika; Fajardo, Diego; Fang, Hui; Frank, Margaret H.; et al. (Frontiers in Plant Science, 2018)
Current morphometric methods that comprehensively measure shape cannot compare the disparate leaf shapes found in seed plants and are sensitive to processing artifacts. We explore the use of persistent homology, a topological method applied as a filtration across simplicial complexes (or more simply, a method to measure topological features of spaces across different spatial resolutions), to overcome these limitations. The described method isolates subsets of shape features and measures the spatial relationship of neighboring pixel densities in a shape. We apply the method to the analysis of 182,707 leaves, both published and unpublished, representing 141 plant families collected from 75 sites throughout the world. By measuring leaves from throughout the seed plants using persistent homology, a defined morphospace comparing all leaves is demarcated. Clear differences in shape between major phylogenetic groups are detected and estimates of leaf shape diversity within plant families are made. The approach predicts plant family above chance. The application of a persistent homology method, using topological features, to measure leaf shape allows for a unified morphometric framework to measure plant form, including shapes, textures, patterns, and branching architectures.